2009
DOI: 10.1021/es901631p
|View full text |Cite
|
Sign up to set email alerts
|

Separator Characteristics for Increasing Performance of Microbial Fuel Cells

Abstract: Two challenges for improving the performance of air cathode, single-chamber microbial fuel cells (MFCs) include increasing Coulombic efficiency (CE) and decreasing internal resistance. Nonbiodegradable glass fiber separators between the two electrodes were shown to increase power and CE, compared to cloth separators (J-cloth) that were degraded over time. MFC tests were conducted using glass fiber mats with thicknesses of 1.0 mm (GF1) or 0.4 mm (GF0.4), a cation exchange membrane (CEM), and a J-cloth (JC), usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(140 citation statements)
references
References 21 publications
7
129
2
2
Order By: Relevance
“…The hydrogen evolution reaction often limits the overall MEC performance and cathodes with a larger surface area have demonstrated an increase in hydrogen production and current density (Call et al, 2009). Also, both MFC and MEC tests have demonstrated that the maximum power output can be increased by reducing the distance between the electrodes (Ghangrekar and Shinde, 2007;Liu et al, 2005a;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen evolution reaction often limits the overall MEC performance and cathodes with a larger surface area have demonstrated an increase in hydrogen production and current density (Call et al, 2009). Also, both MFC and MEC tests have demonstrated that the maximum power output can be increased by reducing the distance between the electrodes (Ghangrekar and Shinde, 2007;Liu et al, 2005a;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A thick aerobic biofilm on the cathodes may function as a diffusion barrier to H + transfer to the catalyst site (Zhang X. et al, 2009;Ahmed, 2011), and it can severely block OH − transport outside the electrode, resulting in an significant OH − accumulation in the cathode microenvironment and thus a lower cathode potential (Yuan et al, 2013); the aerobic bacteria may consume a portion of the available oxygen at the catalytic sites and thus reduce the oxygen reduction kinetics Yuan et al, 2013); the EPS of attached microorganisms may also cause catalyst poisoning. Up to now, only the mechanisms of blockage of OH − and oxygen transfer by the cathodic biofilms have been demonstrated Yuan et al, 2013), the mechanisms how the aerobic biofilm affects cathode performance still need to be investigated.…”
Section: Reducing the Cathode Deteriorationmentioning
confidence: 99%
“…Up to now, only the mechanisms of blockage of OH − and oxygen transfer by the cathodic biofilms have been demonstrated Yuan et al, 2013), the mechanisms how the aerobic biofilm affects cathode performance still need to be investigated. As a result of biofilm growth, an increased internal resistance coupled with a decreased electricity (power) generation of MFCs was obtained in many studies (Cheng et al, 2006;Yang et al, 2009;Zhang X. et al, 2009;Zhang F. et al, 2011a). Therefore, it is important to develop effective methods to minimize the cathode bacterial growth for a better long-term performance of MFCs.…”
Section: Reducing the Cathode Deteriorationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, Nafion used in the MFCs is not an efficient proton specific membrane but actually a cation specific membrane (Rozendal et al, 2006). Subsequent studies have implied that anion-exchange or bipolar membranes has better properties than cation exchange membranes regarding to cell performance (Zhang et al, 2009). Two promising applications of MFCs in the future are wastewater treatment and electricity generation (Feng et al, 2008 andKaturi &Scott, 2010).…”
Section: Microbial Fuel Cellsmentioning
confidence: 99%